Economic prediction of medal wins at the 2014 Winter Olympics - Andreff, M.; Andreff, W. (Ekonomika a Management, 2011)
To the best of our knowledge nobody has attempted to elaborate on an economic model for predicting medal wins at the Winter Olympics so far. This contrasts with Summer Olympics for which about thirty studies have estimated economic determinants of sporting performances (among which Andreff, 2001; Ball, 1972; Clarke, 2000; Grimes et al., 1974; Jiang & Xu, 2005; Levine, 1974; Nevill et al., 2002; Novikov & Maximenko, 1972; Pfau, 2006). Some publications have even provided predictions about medal wins at the next Olympic Games (Bernard, 2008; Bernard & Busse, 2004; Hawksworth, 2008; Johnson & Ali, 2004; Johnson and Ali, 2008; Maennig & Wellebrock, 2008; Wang & Jiang, 2008). Our own model has exactly predicted 70% of medal wins at the 2008 Beijing Olympics and correctly (with a small error margin) 88% of the sporting outcomes at these Games (Andreff et al., 2008 & Andreff, 2010). In this paper, we would take stake of the good predictions achieved with our model for Summer Olympics to adapt it in view of forecasting the distribution of medal wins per nation at the 2014 Sochi Winter Games.